PERAN PELAYANAN KESEHATAN DALAM MENCEGAH TERJADINYA KEKAMBUHAN PADA PASIEN SKIZOFRENIA - , Wijaya Aji, Prof. Dr. dr. H. Soewadi, MPH, Sp.KJ(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The participation of society is the main role for the succees, continuity and independency of health development, including mental health development. The society participation on developing mental health comes by living healhty, organizing will or health services to funding the operational especially mental health, for example schizophrenia. World Health Organization predict about 450 million citizen are suffering schizophrenia. In Indonesia is about 6-9 per 1000 citizen. Schizophrenia is severe mental illness, which is very stressfull, not only for the patient but also for their family. Itâs not easy to preventing relaps in mental disorder including schizophrenia. Until now, the causing of mental illness are still being argued eventhough thereâs many study discus about it. Commonly, mental illlness occur by many factors. These factors are, biology, psychology and sociocultural. The aims of this study are to identify the role of health services on preventing of schizophrenia patient. The study method is an observational study using cross sectional design and analize with linier regression statistic method. The studyâs place is at RSJ. Prof. Dr. Soeroyo Magelang, subjects are hospitalized patient in Intensive Care Unit from November âDesember 2010. The result of this research shows that health service are significantly preventing relaps (p = 0,001). Conclusion of this research is, more dificult or less health services recieved by respondent, more higher their chance to relaps, or in another word, better health services, bigger chance for them for preventing the relaps